Pendekatan MOOC dalam kalangan pelajar asas keusahawanan: perspektif psikologi - Norhaiza Khairudin; Aryati Juliana Sulaiman; Marhaiza Ibrahim; Ahmad Zamil Abd Khalid; Mohd Noor Abdul Hamid (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study set out to investigate the use of Massive Online Open Courses (MOOCs) to improve students' teamwork skills in group project activities for the Fundamentals of Entrepreneurship course among students majoring in Accounting at Universiti Utara Malaysia (UUM). Among the group assignments for the Fundamentals of Entrepreneurship course are the preparation of business plans and website development. However, the output produced was found to be unsatisfactory and failed to be completed within the allotted time. This is due to the problem of the lack of cooperation between group members and the time constraints faced by the students. Therefore, the objective of this study is to examine how the use of MOOCs can help improve the psychological well-being of students in carrying out group project activities in the Fundamentals of Entrepreneurship course conducted online. This study was conducted using action research. Findings show that learning through MOOCs is an effective method to improve teamwork skills and improve the psychological well-being of Fundamental of Entrepreneurship students. From a psychological point of view, students feel that by using MOOCs platforms such as chat rooms and forums, they are able to improve their teamwork skills to help them complete their group projects with better quality and excellence.